MiRNases: Novel peptide-oligonucleotide bioconjugates that silence miR-21 in lymphosarcoma cells. (April 2017) - Patutina, Olga A.; Bichenkova, Elena V.; Miroshnichenko, Svetlana K.; Mironova, Nadezhda L.; Trivoluzzi, Linda T.; Burusco, Kepa K.; Bryce, Richard A.; Vlassov, Valentin V.; Zenkova, Marina A.
Abstract: MicroRNAs (miRNAs) are active regulators in malignant growth and constitute potential targets for anticancer therapy. Consequently, considerable effort has focused on identifying effective ways to modulate aberrant miRNA expression. Here we introduce and assess a novel type of chemically engineered biomaterial capable of cleaving specific miRNA sequences, i.e. miRNA-specific artificial ribonucleases (hereafter 'miRNase'). The miRNase template presented here consists of the catalytic peptide Acetyl-[(LeuArg)2 Gly]2 covalently attached to a miRNA-targeting oligonucleotide, which can be linear or hairpin. The peptide C-terminus is conjugated to an aminohexyl linker located at either the 3′- or 5′-end of the oligonucleotide. The cleavage efficacy, structural aspects of cleavage and biological relevance of a set of these designed miRNases was assayed with respect to highly oncogenic miR-21. Several miRNases demonstrated effective site-selective cleavage of miR-21 exclusively at G-X bonds. One of the most efficient miRNase was shown to specifically inhibit miR-21 in lymphosarcoma cells and lead to a reduction in their proliferative activity. This report provides the first experimental evidence that metallo-independent peptide-oligonucleotide chemical ribonucleases are able to effectively and selectively down-regulate oncogenic miRNA in tumour cells, thus suggesting their potential in development of novel therapeutics aimed at overcoming overexpression of disease-related miRNAs. Graphical abstract: